Camino, metafísica y claro (2017)
This work is a reflection based on the thought of Heidegger, mainly of the texts: What is metaphysics? (1929), Epilogue to what is metaphysics (1943) and Introduction to what is metaphysics? (1949). This reflection is centered in two central themes, metaphysics and ethics. I seek to develop metaphysics as a path that the human being travels to experience this same metaphysics and thus be interpellated by the Being. I rely on the ontological difference made by Heidegger to raise the ontological and metaphysical problem in existential terms. That is, in a way in which this question involves the life of the human being, and brings it as an experience, a search and a way.